2020
DOI: 10.1016/j.ypmed.2020.106270
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between social media use and psychological distress among adolescents

Abstract: This study aimed to examine in a longitudinal cohort design whether social media use among adolescents is related to symptoms of social anxiety, depressed mood, and physical symptoms of anxiety over time. As part of the LIFECOURSE study of risk and protective factors for healthy adolescent development, three waves of school-based surveys of adolescents born in Iceland in 2004 were analyzed. Of the 3,914 eligible adolescents, 2,378 gave informed consent. Complete responses for this study were collected from 2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Another study of 440 children from India also showed that problematic social media use was a risk factor of depression [35]. However, other studies also reported the positive effects of social media on adolescents, such as connecting with friends, greater levels of self-expression [36], and means of education [5]. Therefore, the effects of social media on depressive symptoms among college students remain not confirmed due to the cross-sectional design of this study and the complicated associations between them.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 440 children from India also showed that problematic social media use was a risk factor of depression [35]. However, other studies also reported the positive effects of social media on adolescents, such as connecting with friends, greater levels of self-expression [36], and means of education [5]. Therefore, the effects of social media on depressive symptoms among college students remain not confirmed due to the cross-sectional design of this study and the complicated associations between them.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and amount of time our sample spent on SM are concerning given the association of screen time with many negative health outcomes, including mood symptoms (depression and anxiety), 15,18,23–25 self‐esteem, 17 poorer sleep quality (delayed bedtime, shorter total sleep time), 38 and impact on relationships with others 39 . However, the above associations continue to be called into question as strong longitudinal evidence is lacking 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed the recognition of emotional response types to prevent negative reactions among young people. Distress among students during the COVID pandemic using social media was studied [24]. The results showed a connection between SME and depression, anxiety, and stress.…”
Section: Relationships Between Influencing and Responding Variablesmentioning
confidence: 99%